THE ROLE OF AI IN ENHANCING GREEN MANAGEMENT AND ADVANCING DIGITAL LEAN PRACTICES FOR SUSTAINABLE EFFICIENCY - Pratap, S; Venkatesh, Kandukoori Srivarun (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The integration of Artificial Intelligence (AI) in enhancing green management and advancing digital lean practices marks a pivotal transformation in achieving sustainable efficiency within various sectors. AI's role extends beyond mere automation, serving as a critical tool for data-driven decision-making, resource optimization, and waste reduction. This paper explores the synergistic potential of AI with green management principles and digital lean methodologies to foster environmental stewardship and operational excellence. Through the lens of current technologies such as machine learning, predictive analytics, and IoT, we analyze how AI-driven solutions can significantly reduce environmental footprints, enhance energy efficiency, and streamline production processes. The discussion includes real-world case studies that illustrate substantial improvements in sustainability metrics, including energy consumption, resource utilization, and waste management. However, the adoption of AI also presents challenges, including ethical considerations, data security, and the need for substantial investment in technology and skills development. Despite these hurdles, the compelling benefits of AI for sustainable business practices underscore the importance of continued research, investment, and collaborative efforts in this field. This paper concludes by highlighting future directions for AI in green management and digital lean practices, emphasizing the need for innovative approaches to sustainability that are both efficient and environmentally responsible.